ERYTHROPOIETIN TREATMENT FOR ANEMIA IN CHILDREN WITH CANCER – SINGLE CENTRE EXPERIENCES - Polona Mali; Lidija Kitanovski; Janez Jazbec; Jožica Anžič; Majda Benedik Dolničar (Zdravniški Vestnik, 2004)
Background. Anemia, a common complication during treatment of malignant disease in children, was frequently treated with red blood cell transfusions. Several studies have shown, that the introduction of recombinant human erythropoietin (rh EPO) for treating anemia in patients has been effective in reducing the need for transfusions. Variable doses of EPO from 150 to 900 IU/kg body weight have been used usually three times weekly. Recently some studies showed equally effective once weekly administration of EPO with proposed doses for children of 450 to 600 IU/ kg body weight. Efficacy and safety of once weekly EPO therapy was tested in 8/10 children treated in our Unit for solid tumors and nonHodgkin’s lymphoma. In this article we would like to present our one year experience with EPO treatment. Patients and methods. Patients have subcutaneously received the EPO dose of 600 UI/ kg body weight once weekly. Hemoglobin response and transfusion needs before and during treatment with EPO were analyzed. Results. Response was seen in 7/8 of patient, with increased hemoglobin level and lower transfusion needs. Only one patient was poor responder at first, but responded perfect after twice weekly EPO application. No adverse reaction related to EPO therapy was observed. Conclusions. Our experience with treating anemia in pediatric cancer patients who undergo intensive and aggressive chemotherapy treatment regimens are good and promising. Once weekly dosage regimen is child friendly and acceptable way of treating anemia.